Assessment of preschool and pre-school children - Agata Wawryków; Katarzyna Korabiusz; Monika Stecko; Joanna Harasimowicz; Paweł Harasimowicz (Kazimierz Wielki University, 2019)
Physical activity is the natural, physiological need of the child, which at the same time determines its proper development. In the pre-school period there is a golden age of motoriness, ie the time when the child acquires new skills the fastest, but also a great improvement in the precision and complexity of motor activities. The overall change has a positive effect on the improvement of motor skills. The Modified Wroclaw Physical Fitness Test should be used to assess the motor skills of children in pre-school and school age. The Wrocław Test was characterized briefly. Research has shown that motor efficiency of children is significantly worse than individuals in the same age from 20 years ago.